Consumption, Informal Markets, and the Underground Economy Hispanic Consumption in South Texas - Pisani, M. (Palgrave Macmillan US : Imprint: Palgrave Pivot, 2013)
Using original qualitative ethnographic field interviews and quantitative field survey results, Consumption, Informal Markets, and the Underground Economy explores the rationale for and model of 'off the books' consumption in a borderlands environment.